(untitled) (Mongolian Geoscientist, 2018)
This study presents the hydrogeochemical implications resulted from Ider River, one of headwaters of Selenge River in northern Mongolia which is a main headwater of Lake Baikal in southeastern Russia, being included in a drainage basin of the North Arctic Ocean. Surface water and groundwater were collected and estimated with hydrogeochemical analyses of major ionic compositions in order to determine water quality in the catchment of Ider River in northern Mongolia. Result shows that the downstream of Ider River is more polluted than upstream of Ider River and Khunjil River, an inflow of the Ider River. Surface water of Ider River and groundwater in the catchment of the Ider River are comparable with their anions and cations. Ider River is highly enriched with an anion of Cl- in 2-3 times, cations of Na++K+ in 2-3 times and NH4+ in 0.5-1.0 times than those in groundwater in the catchment of Ider River. The hydrogeochemical results show that the surface water of Ider River is mainly polluted by solid wastes along its valley. More investigations with detail geochemical analyses are needed from the large rivers comprising surface water resource in Mongolia to review the hydrological evolution in Mongolia and Central Asia in the late Holocene.